Prenatal genetic counselling for psychiatric disorders. (23rd August 2016) - Inglis, Angela; Morris, Emily; Austin, Jehannine
Abstract: Psychiatric disorders like schizophrenia, bipolar disorder, depression, anxiety, and obsessive–compulsive disorder are common disorders with complex aetiology. They can exact a heavy toll on the individual with the condition and can have significant impact on family members too. Accordingly, psychiatric disorders can arise as a concern in the prenatal context – couples may be interested in learning about the chance for their child to develop the illness that manifests in the family and may be interested in discussing options for prenatal testing. However, the complex nature of these conditions can present challenges for clinicians who seek to help families with these issues. We established the world's first specialist genetic counselling service of its kind in Vancouver, Canada, in 2012, and to date, have provided counselling for ~500 families and have demonstrated increases in patients' empowerment and self efficacy after genetic counselling. We draw on our accumulated clinical experience to outline the process by which we approach prenatal genetic counselling for psychiatric disorders to assist other clinicians in providing thoughtful, comprehensive support to couples seeking out this service. © 2016 John Wiley & Sons, Ltd.